Characteristics of infertile couples - Akhter, S; Alam, H; Khanam, NN; Zabin, F (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):121-127 The abstract of this article is available on the PubMed website